2016
DOI: 10.5505/tjtes.2016.36932
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Inguinal Hernia in High-risk Geriatric Patients: Should it be Elective or Emergent?

Abstract: BACKGROUND: Elderly patients are more prone to have inguinal hernia due to weakened abdominal musculature. However, surgical repair of inguinal hernia (SRIH) may not be performed or may be delayed due to greater risk in presence of comorbidities. Present study is investigation of outcome of elective and emergency SRIH in geriatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
(18 reference statements)
0
9
0
5
Order By: Relevance
“…Çalışmamızda; hastaların 13'ünde (%81,2) yandaş hastalık mevcut olup; bu hastaların 10'unda (%62,5) koroner arter hastalığı ile hipertansiyon, 7'sinde (%43,7) DM, 6'sında (%37,5) KOAH mevcuttu. İleri yaşlı hasta grubunda inguinal herni cerrahi sonuçlarını incelendiğimiz çalışmamızda eşlik eden yandaş hastalık oranları literatür ile uyumlu olmasına rağmen; eşlik eden KOAH varlığı çalışmamızda daha düşük oranda saptanmıştır (10).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Çalışmamızda; hastaların 13'ünde (%81,2) yandaş hastalık mevcut olup; bu hastaların 10'unda (%62,5) koroner arter hastalığı ile hipertansiyon, 7'sinde (%43,7) DM, 6'sında (%37,5) KOAH mevcuttu. İleri yaşlı hasta grubunda inguinal herni cerrahi sonuçlarını incelendiğimiz çalışmamızda eşlik eden yandaş hastalık oranları literatür ile uyumlu olmasına rağmen; eşlik eden KOAH varlığı çalışmamızda daha düşük oranda saptanmıştır (10).…”
Section: Discussionunclassified
“…Literatürde 70 yaş ve üzeri inkarsere inguinal herni nedeniyle yapılan acil cerrahi girişimler sonrasında mortalite oranı %4-20 olarak rapor edilmektedir. Işıl ve arkadaşlarının yapmış oldukları çalışmada inkarsere inguinal herni nedeniyle acil cerrahi girişim uygulanan geriatrik hastalarda barsak rezeksiyon oranı %21 olarak belirtilmiştir (10). Çalışmamızda hastaların 7'sine (%43,8) nekrotik görünüm nedeniyle barsak rezeksiyonu yapılmış ve mortalite oranı %18,7 olarak bulunmuştur.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…It has been shown that elective inguinal hernia repair carries a mortality rate in the elderly patients similar to that in the general population (4,5). In addition, emergency inguinal hernia surgery is associated with remarkably higher morbidity and mortality rates than elective repairs (6,7). Planned herniorrhaphy under local anesthesia seems more acceptable today even for patients older than 80 years (8).…”
Section: Introductionmentioning
confidence: 99%